Communicating about online health information with patients: Exploring determinants among telemental health providers - Samantha R. Paige; Carma L. Bylund; Hattie Wilczewski; Triton Ong; Janelle F. Barrera; Brandon M. Welch; Brian E. Bunnell (Elsevier, 2023)
Objective: To investigate determinants of telemental health (TMH) providers' openness to discuss and confidence to use online mental health information with patients, focusing on providers' eHealth literacy and perceived usefulness of online MH information. Methods: TMH providers (N = 472) completed a web-based survey with questions about discussing and using online health information with patients, perceived usefulness of the Internet as a source of patient information, and eHealth literacy. Results: Providers were open to discussing online health information with patients if they were not treating substance abuse disorders (b = −0.83), felt the Internet was a useful resource (b = 0.18), and felt confident in their skills to evaluate the online information (b = 0.21). Providers were confident using online health information if they worked in a small clinic (b = 0.37), felt the Internet was a useful resource (b = 0.31), knew where to access relevant online health information (b = 0.13), and had skills to help their patients find (b = 0.17) and evaluate (b = 0.54) online information. Conclusion: TMH providers are likely to use online health information resources if they know where and how to find them and perceive the Internet as a useful resource. Innovation: To effectively discuss online health information with patients, providers require skills to evaluate the information with patients.